Fluoroquinolonas em amostras aquosas ambientais e em teleósteos : quantificação, avaliação de toxicidade e ensaios de biotransformação - Denadai, Marina (Universidade Federal de São Carlos, 2015)
The presence of drugs in the environment is an important issue in environmental risk assessment. The fluoroquinolones represent a class of compounds widely used in human and veterinary medicine, and its apport in the environment is continuous and lacking of monitoring. In this scope, it is important to evaluate the levels of these compounds in the environment and their toxicological impact on aquatic organisms. The present study discuss the development and validation of analytical methods for direct injection of samples using liquid chromatography coupled to mass spectrometry for multiresidual determination of fluoroquinolones in effluents of São Carlos – SP, and toxicity tests of ciprofloxacin (CIP) on fish. For monitoring of effluent samples, six fluoroquinolones were evaluated: CIP, gemifloxacin, moxifloxacin, ofloxacin, enrofloxacin, and norfloxacin (NOR). In effluent samples from wastewater treatment plant, CIP and NOR were quantified at concentrations of 195 ng L-1 and 270 ng L-1, respectively. Toxicity studies of CIP in species of O. niloticus exposed to different concentrations (0.5, 1.0 and 5.0 μg L-1) for periods of 7 and 14 days were evaluated by enzymatic and non-enzymatic systems. The biochemical assays demonstrated that fishes were not able to perform the detoxification, which was evidenced by the severe damage in their cells, especially on the gills and liver of the fishes. In vitro studies were carried out in species of O. mykiss, evaluating the biotransformation and bioaccumulative potential of some drugs commonly used in fish farms, including fluoroquinolones. The results using this in vitro model corroborate to the understanding of similarities and differences among different species of fish, as well as the assessment of environmental impact due to these compounds present in the environment.
Fluoroquinolones in aqueous samples and teleost : quantification, toxicity assessment and biotransformation assays
Keywords: Fluoroquinolonas; Amostras ambientais aquosas; Cromatografia líquida de alta eficiência; Estresse oxidativo; Biotransformação; CIENCIAS EXATAS E DA TERRA::QUIMICA